SPECIFIC CHARACTERISTICS OF THE FOUNDATIONS OF ARTISTIC CREATIVITY IN THE TYPES AND GENRES OF FINE ART - Amanullayev Abdinabi; Tahirova Rayhona (Web of Journals Publishing, 2024)
The study of visual arts is very important for every student. As a result, the cultural wealth created by humanity only helps to understand the laws of development that have remained in the past or are being created, to get acquainted with rare monuments, and to approach life in a broader and more comprehensive way. There are many types of art. They are music, cinema, theater, choreography, visual arts and others. Art that usually represents existence in pictorial images, shapes, spatial extent or plane (on paper surface, wall surface, etc.) is called visual art. As long as the artist depicts the real existence in his works, he never copies it mechanically.
Keywords: Still life, animalistic, landscape, architecture, applied art, fine art, graphics, sculpture, avant-garde, impressionism, cubism, mosaic, stained glass, painting, relief, bas-relief, go-relief, fresco.